1999
DOI: 10.1161/01.atv.19.3.767
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Perivascularl-Arginine Delivery Increases Total Vessel Area and Reduces Neointimal Thickening After Experimental Balloon Dilatation

Abstract: The aim of this study was to evaluate whether vascular remodeling and neointimal thickening occur after balloon dilatation of the nonatherosclerotic rabbit carotid artery, and whether both processes are influenced by continuous perivascular delivery of L-arginine or the nitric oxide synthase inhibitor NG-nitro-L-arginine methyl ester (L-NAME). In the first experiment, histological and morphometric evaluation of arteries was performed at different time points after balloon dilatation: 10 minutes (n=7), and 1 (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 49 publications
(36 reference statements)
1
14
0
Order By: Relevance
“…A number of studies using experimental balloon angioplasty demonstrated the protective role of NO derived from eNOS on vascular remodeling characterized by neointimal formation with the use of eNOS gene transfer or the administration of L-arginine, a substrate for NO. [7][8][9]16,17 However, in the balloon angioplasty-induced vascular remodeling model, the endothelium is injured, and the role of NO produced from the endothelium cannot be fully elucidated. Therefore, the use of the vascular remodeling model in which the endothelium remains intact during the lesion formation process would be required to elucidate directly the role of NO from the endothelium on remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies using experimental balloon angioplasty demonstrated the protective role of NO derived from eNOS on vascular remodeling characterized by neointimal formation with the use of eNOS gene transfer or the administration of L-arginine, a substrate for NO. [7][8][9]16,17 However, in the balloon angioplasty-induced vascular remodeling model, the endothelium is injured, and the role of NO produced from the endothelium cannot be fully elucidated. Therefore, the use of the vascular remodeling model in which the endothelium remains intact during the lesion formation process would be required to elucidate directly the role of NO from the endothelium on remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Failure to block inducible NO synthase has been shown in other reports [13, 14]. The extent to which L-NAME or L-NA inhibit inducible NO synthase is of crucial importance because this isoform is expressed in many pathophysiological conditions [15].…”
Section: Introductionmentioning
confidence: 88%
“…Perivascular delivery of L-arginine reduced vascular remodeling and neointimal thickening after balloon dilatation of rabbit coronary artery [27]. In addition, intravenous infusion of L-arginine enhanced cardiac performance in patients with severe congestive HF, mainly by affecting systemic vascular resistance [28] increasing maximum vasodilatation during reactive hyperemia and reducing peripheral resistance in patients with HF [29,30].…”
Section: Discussionmentioning
confidence: 97%